Physical and functional interaction of carbonic anhydrases and nbce1 Na+/HCO3- cotransporter in the hear: the metabolon revisited - Alvarez, Bernardo (2012)
To allow the control of their intracellular pH (pHi) and bicarbonate (HCO3 - ) levels, cells express HCO3 - transport proteins (NBC) that rapidly and selectively move HCO3 - across the plasma membrane. In the heart electroneutral NBCn1 and electrogenic NBCe1 Na+ /HCO3 - cotransporters facilitate the transmembrane movement of HCO3 - ions into cardiomyocytes, as a response to acid loading. NBCe1 associates with carbonic anhydrases (CA), the enzymes that catalyze the reversible conversion of CO2 to HCO3 - , to form a transport metabolon, a weakly associated complex of sequential metabolic enzymes. NBCe1 physically/functionally interact with the isoforms II, IV, and IX of CA, to increase the HCO3 - flux through cell membranes. NBCe1 and CAs interaction occurs in different cellular compartments in the heart muscle. Physiologically, the NBCe1/CA complex could contribute to the removal of H+ ions accumulated as the result of the contractile activity of the cardiac muscle cell, and this process may occur at the surface sarcolemma (CAII-NBCe1-CAIV complex) or at the ttubule (CAII-NBCe1-CAIX complex) of the cardiomyocyte. Pathologically, upregulation of the NBCe1/CA metabolon system upon ischemic/hypoxic conditions of the heart would favor the hypertrophic growth of the cardiac cells.